Towards a conceptual framework for understanding the implementation of Internet-based self-service technology - Naidoo, Thavandren Ramsamy (2013)
In the past decade, there has been rampant growth in healthcare service delivery options, based on the Internet and related information and communication technology. As a result, there is a great deal of expectation among national governments, regulators, healthcare organisations, and other stakeholders about the role of the Internet in healthcare service provision. Given the global crisis in healthcare services generally and the funding of healthcare services specifically, a number of policymakers view the advances in Internet-based self-service technology as a potential enabler of more efficient and effective healthcare service delivery. Proponents of consumer-driven healthcare in particular who seek to use the Internet to make consumers more informed about healthcare funding decisions and to reduce the cost of servicing consumers have been actively experimenting in this area. Despite the accelerating growth in the deployment of Internet-based self-service technologies, their protracted uptake by users is giving rise to concerns about the effectiveness of the implementation and acceptance of these contemporary forms of service delivery. Furthermore, little is known about how the social healthcare context shapes Internet-based self-service technology implementations. This thesis presents an in-depth qualitative case study that documents a healthcare insurer’s efforts to implement an online self-service technology for the period 1999 to 2005. A research framework was adopted that draws on key theoretical concepts from structuration and actornetwork theory (ANT) to link the social context to implementation processes. These two conceptual lenses, which are compatible with the thesis’s interpretive stance, reveal several new insights, confirming that the challenges associated with the implementation of information system innovations such as Internet-based self-service technologies cannot be understood in isolation. From a structuration perspective analysing the various enactments of self-service provision of healthcare afforded a deeper understanding of how social practices influence the design and use of the technology. From an ANT perspective, the study showed how the major translations in the design and use of the self-service technology emerged from a process where technological and social elements co-evolved. This study also reveals that the implementation problems and opportunities facing this particular healthcare insurance organisation were historical and systemic. This approach demonstrates that the complex interdependencies and interactions among contrasting social, political, economic and technological issues shaped the contemporary channel as it exists today and therefore advances theory in yet another important way. Using the insights obtained from these two theories, a conceptual framework was derived. The conceptual framework demonstrates that in order to develop a comprehensive understanding of Internet-based self-service technology implementation, such an analysis must incorporate the interconnectedness of four perspectives – meaning, process, context and the technology artefact – and their respective conceptual elements from both structuration and actor-network theory. Future studies attempting to deepen our understanding of information systems implementation can also provide constructive insights by focusing on the interdependent, interconnected and historical nature of the implementation phenomenon. Some important practical applications for future self-service technology implementations are also discussed. === Thesis (PhD)--University of Pretoria, 2009. === Informatics === unrestricted